Acanthosis Nigricans Associated with Morbid Obesity and Colorectal Adenocarcinoma - J. Li; A. Yazdabadi; R. Sinclair (Case Reports in Dermatological Medicine)
We report a case of a morbidly obese 32-year-old man presenting with acanthosis nigricans in the setting of Duke's B adenocarcinoma of the hepatic flexure.